2020
DOI: 10.22271/chemi.2020.v8.i6p.10912
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of coir pith for fluidized bed gasification

Abstract: Biomass characteristics are necessary for the proper selection of the gasification system and to design and evaluate the performance of biomass gasifiers. The coir pith is analyzed for its physical properties, chemical composition and kinetic parameters. The mean particle size of coir pith was found to be 0.551 mm. The relative size range of the coir pith was found to be 0.817. The bulk density, porosity and particle density of coir pith were found to be 87.0 kg m -3 , 71.4% and 305.0 kg m -3 respectively. Coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Alauddin et al (2010) presented the merits of gasification of lignocellulosic biomass in fluidized beds for renewable energy development. Ramjani et al (2020) showed the characterization of Coir pith for fluidized bed gasification. This 205 Environment Conservation Journal paper reports the development of a lab model Fluidized Bed Gasifier (FBG), which can handle low density and leafy biomass materials like rice husk, saw dust, bagasse, tree leaves etc.…”
Section: Introductionmentioning
confidence: 99%
“…Alauddin et al (2010) presented the merits of gasification of lignocellulosic biomass in fluidized beds for renewable energy development. Ramjani et al (2020) showed the characterization of Coir pith for fluidized bed gasification. This 205 Environment Conservation Journal paper reports the development of a lab model Fluidized Bed Gasifier (FBG), which can handle low density and leafy biomass materials like rice husk, saw dust, bagasse, tree leaves etc.…”
Section: Introductionmentioning
confidence: 99%